A Validation Study for the Use ofROS1Immunohistochemical Staining in Screening forROS1Translocations in Lung Cancer. Issue 7 (July 2016) - Viola, Patrizia; Maurya, Manisha; Croud, James; Gazdova, Jana; Suleman, Nadia; Lim, Eric; Newsom‐Davis, Tom; Plowman, Nick; Rice, Alexandra; Montero, Angeles M.; de Castro, David Gonzalez; Popat, Sanjay; et al.
ABSTRACT : Introduction: : The presence of ROS proto‐oncogene 1, receptor tyrosine kinase gene ( ROS1 ) rearrangements in lung cancers confers sensitivity to ROS kinase inhibitors, including crizotinib. However, they are rare abnormalities (in ˜1% of non–small cell lung carcinomas) that are typically identified by fluorescence in situ hybridization (FISH), and so screening using immunohistochemical (IHC) staining would be both cost‐ and time‐efficient. Methods: : A cohort of lung tumors negative for other common mutations related to targeted therapies were screened to assess the sensitivity and specificity of IHC staining in detecting ROS1 gene rearrangements, enriched by four other cases first identified by FISH. A review of published data was also undertaken. Results: : IHC staining was 100% sensitive (95% confidence interval: 48–100) and 83% specific (95% confidence interval: 86–100) overall when an h‐score higher than 100 was used. Patients with ROS1 gene rearrangements were younger and typically never‐smokers, with the tumors all being adenocarcinomas with higher‐grade architectural features and focal signet ring morphologic features (two of five). Four patients treated with crizotinib showed a partial response, with three also showing a partial response to pemetrexed. Three of four patients remain alive at 13, 27, and 31 months, respectively. Conclusion: : IHC staining can be used to screen for ROS1 gene rearrangements, with patients herein showing a response to crizotinib. Patients with tumors that test positive according to IHC staining but negative according to FISH were also identified, which may have implications for treatment selection.